The Effect of Community Behavior on The Incidence of Malaria in Sungai Raya Kepulauan - Pusposari, Dewi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
The spread of malaria is determined by factors called Host (host), Agent (plasmodium parasite) and Environment (Environment). The spread of malaria occurs when the three components above support each other. Basically every person can be infected by the agent or the cause of the disease and is the breeding place or the propagation agent (plasmodium parasite). Behavior of society is human behavior or activity of man itself that can support the happening of malaria disease. The purpose of this study was to analyze the effect of community behavior on the incidence of malaria in Sungai Raya Kepulauan Subdistrict, Bengkayang District in 2017. This research type was observational analytic with cross sectional research design. This study wanted to see the effect of community behavior on the incidence of malaria disease during the period of January to July 2017 where two villages (Karimunting and Sungai Keran) become sample of research location. The results obtained from this study there was the influence of behavioral use of bed nets (sometimes) to the incidence of malaria with p-value 0.048. Advice can be given is to avoid and prevent mosquito bites by improving the behavior of clean and healthy life and still use the correct mosquito net while sleeping. Keywords: Malaria, Behavior, Mosquito